2019
DOI: 10.1177/0003122418821339
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Neglect: Limited Liability Companies and Housing Disinvestment

Abstract: Sociological accounts of urban disinvestment processes rarely assess how landlords' variable investment strategies may be facilitated or constrained by the legal environment. Nor do they typically examine how such factors might, in turn, affect housing conditions for city dwellers. Over the past two decades, the advent and diffusion of the limited liability company (LLC) has reshaped the legal landscape of rental ownership. Increasingly, rental properties are owned by business organizations that limit investor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…With a limited supply of public and nonprofit housing, policy solutions seeking a broad impact must inevitably target private landlords, who serve as gatekeepers for the overwhelming majority of US renters. This focus aligns with research indicating that private landlords' decisions to set rent and screening criteria, accept or reject housing vouchers, and evict and select tenants significantly shape renters' housing experiences (Rosen 2014;Desmond 2016;Greif 2018;A. Travis 2019).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…With a limited supply of public and nonprofit housing, policy solutions seeking a broad impact must inevitably target private landlords, who serve as gatekeepers for the overwhelming majority of US renters. This focus aligns with research indicating that private landlords' decisions to set rent and screening criteria, accept or reject housing vouchers, and evict and select tenants significantly shape renters' housing experiences (Rosen 2014;Desmond 2016;Greif 2018;A. Travis 2019).…”
Section: Introductionsupporting
confidence: 70%
“…Recent studies have found that the regulation of private rental owners can yield unintended and negative consequences for renters, particularly vulnerable tenants. Adam Travis (2019) found that legal changes that decreased owners' financial risk prompted some rental owners to let their properties fall into disrepair, a cost borne by tenants, particularly those in poor neighborhoods. Meredith Greif (2018) likewise observed that landlords' business practices are sensitive to the legal environment.…”
Section: The Limits Of Antidiscrimination Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Landlord logics can incorporate a variety of influences. Similar to most economic roles, many scholars assume that profit calculations guide landlord decision making (e.g., Desmond and Perkins 2016;Travis 2019). However, economic sociologists have long identified the role of noneconomic influences, such as social relations, in influencing economic decisions (DiMaggio and Louch 1998;Granovetter 1985).…”
Section: Tenants Landlords and Pathways To Ownershipmentioning
confidence: 99%
“…Today, market forces interact with more subtle prejudices among buyers, realtors, and lenders to produce similar outcomes (Massey and Denton 1998;Trounstine 2018). Where renewed investment does occur in low-income neighborhoods, it disproportionately comes in the form of speculative ownership, and investor-owned properties are more likely to suffer neglect and disrepair (Travis 2019), increasing the risk of exposure to environmental hazards within the home.…”
Section: Place Poverty and Environmental Inequality: A General Frammentioning
confidence: 99%